Enhanced photoelectrochemical conversion performance of ZnO quantum dots sensitized α-Fe2O3 thin films. (4th May 2015) - Ikram, Ashi; Sahai, Sonal; Rai, Snigdha; Dass, Sahab; Shrivastav, Rohit; Satsangi, Vibha R.
Abstract ZnO quantum dots (QDs) sensitized electrodeposited α-Fe2O3 thin films have been investigated for their photoelectrochemical performance at various sensitization times. 24 h ZnO QDs sensitization in α-Fe2O3 thin film exhibited 5.5 fold enhancement in the photocurrent density. This sample shows the highest photocurrent density of 2.84 mA cm−2 at 0.75 V/SCE electrode potential. XRD, HRTEM, EDX, FESEM, UV–visible spectroscopy and Mott–Schottky studies have also been carried out to examine the cause of the improved PEC response of sensitized samples of α-Fe2O3. Enhanced photocurrent exhibited by α-Fe2O3 thin film after ZnO QDs sensitization has been mainly attributed to efficient charge separation due to the presence of ZnO QDs and to the catalytic behavior of ZnO.